(untitled) (Journal of Health, Population and Nutrition, 2010)
Diarrhoeal infections are the fifth leading cause of death worldwide and continue to take a high toll on child health. Mushrooming of slums due to continuous urbanization has made diarrhoea one of the biggest public-health challenges in metropolitan cities in India. The objective of the study was to carry out a community-based health and nutrition-education intervention, focusing on several factors influencing child health with special emphasis on diarrhoea, in a slum of Delhi, India. Mothers (n=370) of children, aged >12-71 months, identified by a door-to-door survey from a large urban slum, were enrolled in the study in two groups, i.e. control and intervention. To ensure minimal group interaction, enrollment for the control and intervention groups was done purposively from two extreme ends of the slum cluster. Baseline assessment of knowledge, attitudes, and practices on diarrhoea-related issues, such as oral rehydration therapy (ORT), oral rehydration salt (ORS), and continuation of breastfeeding during diarrhoea, was carried out using a pretested questionnaire. Thereafter, mothers (n=195) from the intervention area were provided health and nutrition education through fortnightly contacts achieved by two approaches developed for the study—‘personal discussion sessions’ and ‘lane approach’. The mothers (n=175) from the control area were not contacted. After the intervention, there was a significant (p=0.000) improvement in acquaintance to the term ‘ORS’ (65-98%), along with its method of reconstitution from packets (13-69%); preparation of home-made sugar-salt solution (10-74%); role of both in the prevention of dehydration (30-74%) and importance of their daily preparation (74-96%); and continuation of breastfeeding during diarrhoea (47-90%) in the intervention area. Sensitivity about age-specific feeding of ORS also improved significantly (p=0.000) from 13% to 88%. The reported usage of ORS packets and sugar-salt solution improved significantly from 12% to 65% (p=0.000) and 12% to 75% (p=0.005) respectively. The results showed that health and nutrition-education intervention improved the knowledge and attitudes of mothers. The results indicate a need for intensive programmes, especially directed towards urban slums to further improve the usage of oral rehydration therapy. Key words: Community health; Diarrhoea; Interventions; Nutrition education; Oral rehydration solutions; Slums; India DOI: 10.3329/jhpn.v28i6.6603 J HEALTH POPUL NUTR 2010 Dec;28(6):553-559